A "Sudden Outbreak of Tranquility:" Assessing the New Peace in Africa - Menkhaus, Ken (Tufts Archival Research Center, 2005)
Volume 28, Issue 2. Summer Ken Menkhaus considers whether the continent's recent period of relative tranquility is merely a lull in violence or the dawn of a new peace that portends something more permanent.